The effect of leadership style and IT support on lecturer performance during e-learning program with work environment as mediating variable - Haziroh, Awanis Linati; Putra, Febrianur Ibnu Fitroh Sukono; Budiantoro, Risanda Alirastra (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2021)
The lecturer performance appraisal system is the work of lecturers within the scope of their responsibilities which refers to a formal and structured system used as an instrument to measure, assess, and influence work-related traits, control lecturer behavior, including absenteeism rates and work results. Lecturer professionalism must, of course, be related and built through mastery of fundamental competencies in carrying out and completing their duties and work as lecturers, such as professional competence, social competence, and personal competence. The low performance of lecturers is suspect of having reasons such as lack of attention and concern from leaders, for example, less effective leadership styles, less communicative work relationships, lack of harmony, lack of welfare, lack of motivation, lack of a comfortable work environment, and lack of satisfaction felt by the lecturers. Based on these reasons, further research is needed on the influence of leadership style and work environment on lecturer performance in carrying out the teaching and learning process at private universities in Semarang. This research is a quantitative study with a sample of 127 permanent lecturers in the management department of private universities in Semarang. The analytical technique used in this study is path analysis with the results. Among others, leadership style, information technology support, and work environment significantly affect lecturer performance. Furthermore, the work environment can mediate the relationship between leadership style and information technology support on lecturer performance.